IMPLEMENTATION OF THE GLOBAL ACADEMIC COLLABORATION PROGRAM AS STRENGTHENING THE COMPETITIVENESS OF HIGHER EDUCATION - Nuryati Nuryati (Amal Insani Foundation, 2026)
Study: This aims to analyze the implementation of collaborative programs among global academics as a strengthening strategy. Power competition college high. The approach study uses a quantitative explanatory design with a questionnaire from 30 lecturers and leaders/management units. Work in the same international setting in four colleges with disguised height. Data analysis was carried out using Partial Least Squares structural equation modeling (PLS-SEM). The research results show that implementation collaboration is influential, global, academic, positive, and significant to power competition in colleges, with policy institutions as the most dominant factor. Research concludes that global academia is a managerial strategy important for increasing quality, tridharma, and college height. Contribution study. This strengthens the study of internationalization education theoretically and provides implications for leadership colleges in designing policy and governance collaboration and effective and sustainable global academics.